2005
DOI: 10.1007/s12110-005-1007-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of residential locality on parental and alloparental investment among the Aka foragers of the central African Republic

Abstract: In this paper I examine the intracultural variability of parental and alloparental caregiving among the Aka foragers of the Central African Republic. It has been suggested that maternal kin offer higher frequencies of allocare than paternal kin and that maternal investment in infants will decrease when alloparental assistance is provided. Behavioral observations were conducted on 15 eight-to twelve-monthold infants. The practice of brideservice and the flexibility of Aka residence patterns offered a means to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 27 publications
5
115
2
Order By: Relevance
“…If attention to child need, or lack thereof, across developmental periods is based on whether others are available to assist, this may indicate that children's caregiving or social networks strategically target investment. In light of previous research among the Aka, which demonstrated that infants in matrilocal contexts have more frequent access to alloparental investment than those residing patrilocally (Meehan, 2005), we hypothesize that allomothers and the social network in the matrilocal context will buffer the loss of the grandmother. These foci speak to the avenues through which humans have supported lengthy human development and dependency and to whether human cooperative breeding is flexible.…”
mentioning
confidence: 85%
“…If attention to child need, or lack thereof, across developmental periods is based on whether others are available to assist, this may indicate that children's caregiving or social networks strategically target investment. In light of previous research among the Aka, which demonstrated that infants in matrilocal contexts have more frequent access to alloparental investment than those residing patrilocally (Meehan, 2005), we hypothesize that allomothers and the social network in the matrilocal context will buffer the loss of the grandmother. These foci speak to the avenues through which humans have supported lengthy human development and dependency and to whether human cooperative breeding is flexible.…”
mentioning
confidence: 85%
“…An intensive study of Aka hunter-gatherers in central Africa, who purportedly reside in patriclans, illustrates these points. When Meehan (2005) interviewed 15 mothers of infants, 7 were residing matrilocally and 8 patrilocally, but none actually preferred the latter option: 13 said that given the choice, they would be with their mothers, where they and their children would get better care, and two professed indifference. Observational data confirmed that the infants indeed received significantly more care from maternal relatives when residing matrilocally than was provided by paternal kin when they dwelt virilocally.…”
Section: Grandmothering Among Hunter-gatherersmentioning
confidence: 99%
“…Humans are cooperative breeders; we require the contributions of others (alloparents) via care and provisioning to ensure successful reproduction (Hrdy, 2005a(Hrdy, , 2009Mace and Sear, 2005;Meehan, 2005). As alloparental assistance allows mothers to rear multiple dependent offspring, these contributions are important to our reproductive decision making and likely influenced the evolution of human life history and ontogeny (Hrdy, 2005b;Kramer, 2010;Mace and Sear, 2005;Turke, 1988).…”
Section: Cooperative Breeding and Life Historymentioning
confidence: 99%